(untitled) (Journal of Management and Social Sciences, 2023)
Most scholars of electoral politics regard election as the institutionalised means of mass political participation by citizens of a country and a basic means by which people in a democracy hold the government accountable. At the turn of the new millennium, countries around the world have been confronted with major challenges in meeting international standards of electoral integrity. There is a widespread and growing concern that elections globally are marred by serious problems. Nigeria as a country is not immune from these global challenges that have whittled down the integrity of the electoral process. This research examines the relationship between the variables of electoral integrity, and good governance in Nigeria. As a bi-variate study, the research adopts the mixed research method in which both primary and secondary sources of data were qualitatively and quantitatively analysed. The study has a population of 1200 respondents from three states in Nigeria (Kwara, Ekiti and Rivers) using the Taro Yamane statistical formulae. To complement this, forty-five interviewees were purposively selected for both Focus Group Discussions (FGD) and Key Informant Interviews (KII). The study is situated within the prisms of the Principal-Agency-Theory. Findings from the study revealed significant impact of electoral integrity on good governance in Nigeria. Other findings from the study show that the preponderance of post election violence in the 2019 presidential election is attributed to deficiency in electoral integrity. The study recommends the need for significant improvement in the integrity quotient of elections as precondition for the global desire for good governance. Keywords Elections, electoral integrity, good governance, democracy, Nigeria